The tree that came to stay - Quindlen, Anna.; Carpenter, Nancy (New York : Crown Publishers, 1992)
A family finds a way to preserve the feeling of Christmas into the new year by filling a basket with the pine needles from the Christmas tree.
Keywords: Christmas trees -- Fiction; Christmas -- Fiction; Family life -- Fiction